EVALUASI KEBIJAKAN PENGURANGAN PENGGUNAAN KANTONG PLASTIK (STUDI KASUS DI PASAR PABEAN SURABAYA) - Ervin Ghozi Halim; Binti Azizatun Nafi'ah (Halu Oleo University, 2024)
The problem of plastic waste is an important issue, one of which is for the City of Surabaya, therefore the Surabaya City Government formed Perwali Surabaya No. 16 of 2022 concerning Reducing the Use of Plastic Bags. However, in its implementation, there are still many business actors who still use plastic bags, one of which is in the Pabean Market. This study aims to determine the success and provide recommendations for policies to reduce the use of plastic bags in the Pabean Market, Surabaya City. This research uses qualitative research methods, with the technique of determining snowball informants. Data collection techniques were carried out by interview, observation, and documentation methods. The research focuses on policy evaluation theory, namely input, process, outputs, and outcomes. Data analysis techniques are carried out by collecting data, condensing data, presenting data, and drawing conclusions. The results showed that the policy of reducing the use of plastic bags in the Pabean Market has not gone well because it has not fulfilled the evaluation measures, namely input, process, outputs, and outcomes. There needs to be improvements in the implementation of this policy so that obstacles can be overcome and this policy can run well in the future.